Genetic diversity of mango leafhopper, Amritodus atkinsoni (Hemiptera: Cicadellidae) based on mtCOI gene sequences from India. Issue 1 (2nd January 2019) - Choudhary, Jaipal S.; Prabhakar, Chandra S.; Naaz, Naiyar; Lemtur, Moanaro; Das, Bikash; Kumar, Shivendra; Bhatt, Bhagwati P.
Abstract: The mango leafhopper, Amritodus atkinsoni is a serious and an endemic insect pest of mango in India. We analyzed mtCOI gene sequences from six Indian populations of A. atkinsoni for genetic diversity and population structure. The analysis of mtCOI sequence revealed 14 unique haplotypes and a low level of nucleotide diversity. mtCOI gene sequence analysis also revealed that A. atkinsoni specimens were clearly differentiated from other closely related species with a high level of accuracy.